Hemodynamic Definitions, Phenotypes, Pathophysiology, and Evaluation of Pulmonary Hypertension Related to Left Heart Disease - Elizabeth C. Ghandakly; Akshat Banga; Roop Kaw (Journal of Cardiovascular Development and Disease)
Pulmonary hypertension (PH) can develop from multiple etiologic mechanisms and disease states. Of all such conditions, left-sided heart disease (LHD) is commonly understood to be the most common etiology or mechanism. Given the widespread prevalence of left heart disease and the prognostic implications of PH, early diagnosis is imperative. More recently, the diagnostic cut-offs for mean pulmonary arterial pressure as well as peripheral vascular resistance have been lowered to achieve this objective. Despite these revised standards, the current indications for right heart catheterization are mostly aimed at identifying advanced disease. Proven vasodilator therapies for pulmonary arterial hypertension have so far not shown a meaningful role in the management of PH in LHD. This is largely related to the fact that multiple mechanisms and co-morbidities can independently lead to the development of PH in an individual patient. Understanding and identifying those phenotypes remain important in devising future treatment strategies. Molecular pathways that eventually lead to irreversibility of PH can provide another frontier in the pharmacologic management of PH in LHD.